A review on assistive tools for autistic patients - Mohamaddan, Shahrol; Syed Shazali, Syed Tarmiz; Nur Alia, Athirah Mohtadzar (IEEE, 2016)
Persistent difficulties in social skills and social interaction present significant challenges for individuals diagnosed with autism spectrum disorders (ASD). The current literature review provides a comprehensive investigation of studies focused on assistive tools for deficits in social skills or social interaction in those with ASD. Twelve studies that met the inclusion criteria were chosen. Studies were categorized based on Computer-based Intervention (CBI) and Robot-assisted Behavioral Intervention (RBI). Each study were then evaluated on several aspects. Strengths, limitations and outcomes were discussed. All studies showed positive outcomes.